THEORETICAL AND INSTITUTIONAL BASIS OF ASSESSING THE QUALITY OF PRESCHOOL EDUCATION AT THE NATIONAL AND INTERNATIONAL LEVEL (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article discusses the issues of improving the education system through the development of theoretical and institutional aspects of assessing the quality of preschool education, harmonizing national and international approaches to improving the quality of education, improving systematic monitoring mechanisms, and analyzing international standards.